The Virtue Ethics Hypothesis: Is there a nexus between virtues and well-being? - Christian Koch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Why do some people behave pro-socially while others do not? Using an experimental design based on Konow and Earley (JPubE, 2008), I investigate a reason already proposed by Aristotle in his Nicomachean Ethics: He claims that there is a nexus between virtues and well-being and that enduring well-being cannot be achieved by hedonic pleasures and material affluence, but only by virtuous behavior. In order to analyze this hypothesis, I use a within-subject design. Initially, participants answer an elaborated well-being questionnaire and then play six different cooperation games. I examine two questions in connection with the Aristotelian idea: First, do more virtuously behaving subjects report on average higher well-being? Second, if the answer is affirmative, what is the underlying causal relationship? I find a favorable correlation between well-being and virtuous behavior and examine different hypotheses about what leads to virtuous behavior: My experimental data is mostly in line with the hypothesis that virtuous behavior is both a long-run cause as well as a short effect of a specific type of long-run well-being, called eudaimonic well-being. To this extent, I find evidence in favor of a nexus between virtues and well-being.
Keywords: C91; D64; D03; 330